Örgütlerde iç çatışmalar ve yönetimi - Avcı, Ayla (İktisadi Kalkınma ve Sosyal Araştırmalar Derneği, 2020)
Çatışma genel anlamıyla olumsuz bir durumu ifade etmektedir. Toplum, aile ya da kurumlar, hangi alanda yaşanırsa yaşansın çatışma sorunların habercisidir. Herhangi negatif bir durumun ortaya çıkmasında bireyler arası çatışma ortamı oluşmaya başlamaktadır. Herkesin aynı fikri düşünceyi, yöntemi benimsemesi elbette ki mümkün değildir. İnsanlar farklı kişilik özelliklere sahip olarak yaratılmıştır. Dünyadaki huzur ve barış birliğinin sağlanması da ortak bir kural ve kanunlar bütünüyle sağlanmaktadır. Çatışma ortamı karşılıklı çıkar çatışmaları sonucu baş göstermektedir. Özellikle kurumlar, şirketler arasındaki bu sorun çözüm üretme arayışlarını da beraberinde getirmiştir. Makalede şirketlerde yaşanan çatışmaların nedenleri sonuçları ve çözüm yöntemleri incelenmiştir.

Conflict generally expresses negative situation. Society, family or institutions, no metter what area they live in, conflict is a harbinger of the existence of problems. People created according to different personality traits. The beliefs, value judgments, lifestyles, working techniques and methods of each individual vary. Of course, it is not possible for everyone to adopt the same idea, thought and method. Providing tranquility and peace unity in the world is also provided with a common rule and laws. Conflict environment generally emerges as a result of mutual conflicts of interest. Especially in organizations, this problem between managers, individuals and groups brought along the search for solutions. It is not possible to prevent internal conflicts completely due to changing organizational structures, technologies used, employee values, and perception differences in understanding and interpreting events. It is among the most important duties and responsibilities of managers to minimize the conflict environments that occur by examining the reasons of the conflict and whether it will have a positive contribution to the goals and objectives of the organization and to benefit the functioning of the organizations. Peace and harmony balance in working environments in innovative organizational structures will also be positively affected by the efficiency and efficiency levels of organizations. conflict solutions were presented in the study and the evaluation of managers was considered. The article examines the causes, consequences and solution methods of conflicts in organizations, and deals with managing conflict pocesses in a way to benefit the organization.
Internal conflicts and management in organizations
Keywords: Örgüt; İç çatışma; Çatışma yönetimi; Organization; Internal conflict; Conflict management